Study of MWNT/Epoxy Nanocompositesâ Tensile Properties Produced by Resin- Hardener Mixing at Room Temperature - Anindyajati, Dika
Addition of 5 wt% MWNT in MWNT/epoxy nanocomposite showed decrease of tensile properties. Improvement in manufacture methods were done by cleaning the MWNT in acid solution, ultrasonication, precuring, and functionalization. High temperature resin-hardener mixing cause poor interface between epoxy and MWNT. This research will study the effect of resin-hardener mixing at room temperature on nanocomposites’ tensile properties. Parameters of fully cured epoxy matrix were determined by varying curing time. Nanocomposite’s degree of cure were determined by Differential Thermal Analysis (DTA) and Fourier Transform Infrared (FTIR) Spectroscopy. Nanocomposites produced by resin-hardener mixing at room temperature and varied by precuring or without precuring process. Tensile properties of nanocomposite were investigated using tensile test. The results were compared with other research data resulting from resin-hardener mixing at high temperature. Fully cured 5wt% MWNT/epoxy nanocomposites have been made with stiffness as high as 0.779 GPa, and strength as high as 11.1 MPa. Resin-hardener mixing at room temperature showed improvement on epoxy-CNT interface and lowered fraction of void, but induced MWNT agglomeration compared to resin-hardener mixing at high temperature. Precuring also showed improvement on epoxy-CNT interface. However precuring also induced matrices degradation and MWNT agglomeration.